The Bible, sexuality challenges and the development agenda: Zimbabwe’s Tertiary Institutions in Focus - Mwandayi, Canisius (Bible in Africa Studies 25 ERA 4, 2022)
Introduction Since the establishment of learning centres by missionaries during the colonial era (Zvobgo 1996), the word of God has been read and preached ceaselessly to both students and staff. In spite of all these efforts, sexuality challenges in these learning centres and particularly tertiary institutions has remained a hidden transcript that some students not only acquire butoften carry along with, as they leave tertiary life into the job market and often impacting negatively on a country’s developmental efforts as many often succumb to sexually transmitted illnesses, including HIV & AIDS. What happens at colleges and universities defies the common missionary expectation that one becomes better the more he/she is preached to or reads the Bible.